MEKANISME KERJA ROOM ATTENDANT THE ZURI HOTEL PEKANBARU - Azis Riduansyah; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT The working mechanism is a work procedure that has been determined with the aim of making it easier to work on and have the same work result in accordance with a predetermined barometer. In a hotel, housekeeping plays an important role in maintaining the hotel’s reputation, especially room attendants because hotels are synonymous with rooms that are kept clean, comfortable, beauty of rooms are important values for a guest who wants to stay. This study aims to find out the arrangement of work mechanism by management, the operational procedures of a room attendant in making and maintaining a room (make up room) starting with the preparation of the room attendant before starting work (Preparation), priority of makeup room, make up room procedure, and criteria the result of good room attendant work, and room attendant constraints in working with references, namely the book from Rumekso (2002) in the Housekeeping Departement of The Zuri Hotel Pekanbaru. All the data needed for the authors were collected by observation, interviews and documentations techniques. Based on the results of research on the working mechanism of room attendants at The Zuri Hotel Pekanbaru it is said to be good because there are things that are very systematically planned but there are things that are still being improved for management with predetermined procedures. Keywords: Implementation of Tasks, Room Attendant, Room Guest, The Zuri Hotel Pekanbaru